Walled Urban Expansion: A Systematic Mapping of the Literature - Silva, Caio Corte da; Bernardini, Sidney Piochi; Santos, Mariana Rodrigues Ribeiro dos (ANAP Brazil, 2025)
Objective - To systematically review academic production in the field of Architecture and Urbanism, identifying studies that address the relationship between urban planning and the emergence of gated residential developments. Methodology - Systematic Mapping Study, using the combination of terms "Urban Planning" and "Gated Subdivision". Originality/Relevance - The mapping illustrates how current research addresses the phenomenon of walled urban expansion, identifies theoretical gaps, and points to new directions for future investigations. Results - Of the 137 selected studies, 89 are case studies and 35 are literature reviews. The main topics covered are space production (27%), socio-spatial segregation (23%), and economic interests (13%). Theoretical/Methodological Contributions - The predominance of case studies indicates opportunities for alternative methodological approaches. Topics such as the environment are underexplored, suggesting new research directions. Social and Environmental Contributions - The research highlights the need for more inclusive urban policies that reduce physical and symbolic barriers. Environmentally, the results indicate the need for further studies on the environmental impact of walled developments.